2017
DOI: 10.5664/jcsm.6386
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mortality in Relation to Insomnia and Obstructive Sleep Apnea in Korean Patients Studied with Nocturnal Polysomnography

Abstract: Study Objectives: To elucidate the links between the two most prevalent sleep disorders, insomnia and obstructive sleep apnea (OSA), and mortality. Methods: We studied 4,225 subjects who were referred to the Center for Sleep and Chronobiology, Seoul National University Hospital, from January 1994 to December 2008. We divided the subjects into five groups: mild OSA (5 ≤ AHI < 15), moderate OSA (15 ≤ AHI < 30), severe OSA (AHI ≥ 30), insomnia, and a no-sleep-disorder group consisting of subjects without sleep di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The characteristics of normal healthy sleep are a sufficient duration with regular and appropriate timing, and good quality in the absence of disorders and disturbances related to sleep 2 . On the long-term, sleep disturbances not only cause poor activity, fatigue, and decreased cognitive performance, but also increase the risk of early mortality, and several comorbid conditions such as cardiovascular disease, diabetes, hypertension, obesity, cancer, and depression 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 . Thus, getting enough sleep with good quality is important for human health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of normal healthy sleep are a sufficient duration with regular and appropriate timing, and good quality in the absence of disorders and disturbances related to sleep 2 . On the long-term, sleep disturbances not only cause poor activity, fatigue, and decreased cognitive performance, but also increase the risk of early mortality, and several comorbid conditions such as cardiovascular disease, diabetes, hypertension, obesity, cancer, and depression 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 . Thus, getting enough sleep with good quality is important for human health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate-severe OSA was independently associated with a higher mortality risk (aHR = 7.35, 95% CI: 2.40-22.49, P < 0.05). A prospective longitudinal study with an average follow-up duration of 10.5 ± 4.1 years found that age (HR = 1.07, 95% CI 1.06-1.08, P < 0.001), male sex (HR = 1.68, 95% CI 1.24-2.28, P = 0.001), high AHI (HR = 1.01, 95% CI 1.01-1.02, P < 0.001), high periodic limb movement index (HR = 1.014, 95% CI 1.01-1.02, P = 0.002), and low sleep e ciency (HR = 0.949, 95% CI 0.916-0.984, P = 0.004) were signi cantly associated with increased all-cause mortality [22]. A study in Denmark that included 22,135 OSA patients showed that male sex, age > 40 years, DM, hypertension, and CHD were associated with greater mortality risk [23].…”
Section: Discussionmentioning
confidence: 97%
“… 6 OSA is associated with many diseases or disorders such as: cardiovascular diseases, 7 metabolic disorders (i.e., diabetes), 8 gastric disorders (i.e., gastroesophageal reflux disease), 9 respiratory disorders (i.e., asthma), 10 emotional and psychological disorders 11 and increased mortality rates. 12 …”
Section: Introductionmentioning
confidence: 99%